Front and Back Matter for Volume 2 Issue 3, May 2025 - Trends in General Medicine and Public Health, Svāsthya (Svāsthya: Trends in General Medicine and Public Health, 2025)
Volume 2, Issue 3, May 2025 This issue consists of 5 articles contributed by 16 authors affiliated with 11 affiliations from Three countries, including Indonesia (Universitas Jenderal Soedirman, Center of Sustainable Development Goals, Universitas Jenderal Soedirman, Sekolah Tinggi Ilmu Kesehatan Medistra Indonesia, Universitas Muhammadiyah Surakarta, Rumah Sakit Umum Daerah (RSUD) Sumberglagah Mojokerto, Universitas Airlangga, Universitas Syah Kuala, Dr. Zainoel Abidin Hospital, Aceh Emergency Medical Team), India (Uttaranchal Institute of Pharmaceutical Sciences, Uttaranchal University), Turkey (Istanbul Medipol University)